The Cercle Social, the Girondins, and the French Revolution. - Kates, Gary, 1952- (Princeton legacy library., 2014)
Gary Kates reconstructs the history of the Cercle Social, a group of writers and politicians who wielded considerable influence during the French Revolution and whose pioneering interest in women's rights and land reform made their club one of the most progressive in Revolutionary Paris. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these importan.